Metaphor Analysis in Ojo Kumba Futung Letang Dulionong Song Lyrics in Dulolong and Alor Kecil Village - Prasong, Muthiah; Abdullah, Muhammad; Mako, Kusmadi (Devotion: Journal of Community Service, 2022)
The problem in this study is to determine what types of metaphors exist in the lyrics of the song Ojo Kumba Futung letang dulionong in Dulolong Village, Northwest Alor District, Alor Regency, and what their meanings are. The goal of this research was to explain and analyze the metaphor in the lyric of the song Ojo Kumba Futung letang dulionong, which was performed in Dulolong Village, Northwest Alor District, Alor Regency . The author employed qualitative research, which is based on the interpretation of meaning and phenomena or events that occur in society but are difficult to quantify with numbers or other precise measurements. According to the findings of the research, there are numerous types of metaphorical poems in Dulolong village with diverse meanings, some of which have connotations in marriage, others in the lego-lego dance, and even poetry with meanings in brotherhood, which is known as Ojo in the local language. Letang Dulionong Kumba Futung The poem by Ojo Kumba Futung Letang Dulionong has a very positive connotation for the Dulolong community, and it explains the evidence of a close brotherhood. This line was chanted at a gathering of traditional chiefs to work on the Uma Kakang Tribe's traditional dwelling. Poetry plays a vital role in a variety of activities such as traditional parties and weddings, as these poems give art that can help set the tone for these events.